Listeria monocytogenes survival in raw Atlantic salmon (Salmo salar) fillet under in vitro simulated gastrointestinal conditions by culture, qPCR and PMA-qPCR detection methods. (June 2019) - Barretta, Clarissa; Verruck, Silvani; Maran, Bruna Marchesan; Maurício, Leticia dos Santos; Miotto, Marília; Vieira, Cleide Rosana Werneck; Prudencio, Elane Schwinden
Abstract: Because the food matrix is considered as one of the significant factors in regulating colonization of microorganisms in the gastrointestinal tract, this study aimed to evaluate how Listeria monocytogenes survives in raw Atlantic salmon fillet under in vitro simulated gastrointestinal conditions steps. For in vitro gastrointestinal conditions, raw salmon fillet samples were spiked with two L. monocytogenes inoculum levels at 2 and 8 log CFU/g, respectively. L. monocytogenes enumeration was determined using culture-dependent, qPCR and PMA-PCR methods, and these results determined L. monocytogenes recovery rate. The PMA-qPCR method was the most efficient for L. monocytogenes enumeration, mainly after oesophagus-stomach and duodenum steps. The recovery rate was higher than 76%, while to the traditional method this value was lower than 23%. Overall, L. monocytogenes showed stability against the gastrointestinal conditions steps, once the recovery rate was higher than 75%. However, the raw salmon fillet did not contribute to L. monocytogenes stability under in vitro simulated gastrointestinal conditions. The results obtained contribute to understanding L. monocytogenes survival mechanism in a raw fishery product, predicting their behavior during gastrointestinal conditions. Highlights: Listeria monocytogenes showed stabil ity against the gastrointestinal conditions. PMA-qPCR method was the most efficient for Listeria monocytogenes count. Salmon fillet did not contributed to Listeria monocytogenes stability.